Cost-effectiveness of intermittent preventive treatment with dihydroartemisinin-piperaquine versus single screening and treatment for the control of malaria in pregnancy in Papua, Indonesia: a provider perspective analysis from a cluster-randomised trial. Issue 12 (December 2020) - Paintain, Lucy; Hill, Jenny; Ahmed, Rukhsana; Umbu Reku Landuwulang, Chandra; Ansariadi, Ansariadi; Rini Poespoprodjo, Jeanne; Syafruddin, Din; Khairallah, Carole; Burdam, Faustina Helena; Bonsapia, Irene; ter Kuile, Feiko O; Webster, Jayne
Summary: Background: Malaria infection during pregnancy is associated with serious adverse maternal and birth outcomes. A randomised controlled trial in Papua, Indonesia, comparing the efficacy of intermittent preventive treatment with dihydroartemisinin-piperaquine with the current strategy of single screening and treatment showed that intermittent preventive treatment is a promising alternative treatment for the reduction of malaria in pregnancy. We aimed to estimate the incremental cost-effectiveness of intermittent preventive treatment with dihydroartemisinin-piperaquine compared with single screening and treatment with dihydroartemisinin-piperaquine. Methods: We did a provider perspective analysis. A decision tree model was analysed from a health provider perspective over a lifetime horizon. Model parameters were used in deterministic and probabilistic sensitivity analyses. Simulations were run in hypothetical cohorts of 1000 women who received intermittent preventive treatment or single screening and treatment. Disability-adjusted life-years (DALYs) for fetal loss or neonatal death, low birthweight, moderate or severe maternal anaemia, and clinical malaria were calculated from trial data and cost estimates in 2016 US dollars from observational studies, health facility costings and public procurement databases. The main outcome measure was the incremental cost per DALY averted. Findings: Relative to single screening and treatment, intermittent preventive treatment resulted in an incremental cost of US5657 (95% CI 1827 to 9448) and 107·4 incremental DALYs averted (–719·7 to 904·1) per 1000 women; the average incremental cost-effectiveness ratio was 53 per DALY averted. Interpretation: Intermittent preventive treatment with dihydroartemisinin-piperaquine offers a cost-effective alternative to single screening and treatment for the prevention of the adverse effects of malaria infection in pregnancy in the context of the moderate malaria transmission setting of Papua. The higher cost of intermittent preventive treatment was driven by monthly administration, as compared with single-administration single screening and treatment. However, acceptability and feasibility considerations will also be needed to inform decision making. Funding: Medical Research Council, Department for International Development, and Wellcome Trust.